The Impacts of Experiential and Cultural Change towards Chinese college students’ Luxury Consumption: A Cross-group Study between Domestic and Overseas Chinese students - Haoran, Wang (2011)
The past two decades have witnessed the incredible development for global luxury markets, among which emerging economics such as China had stunning appetite for luxuries since 1990s. Not only do Chinese elites purchase luxuries, but middle- and lower-class consumers also show increasing possession rate, including students. The luxury-possession is even more prevalent among overseas Chinese students compared with their domestic counterparts. Few literature works have placed focus on the attributions of their aggressive purchase when they are abroad. This study examines how change of culture and consumer experience could affect overseas Chinese students’ luxury purchase and consumption, which could help practitioners, especially Chinese domestic ones, to develop more effective marketing strategies and make more improvements.